Answer:
6.71
Step-by-step explanation:
→ Find a triangle to use
Tan = Opposite ÷ Adjacent
→ Rearrange to make opposite the subject
Opposite = Tan × Adjacent
→ Substitute in the values
Opposite = Tan (40) × 8
→ Simplify
Opposite = 6.71
Answer:
5, 9, 13, 17, 21, .....
Step-by-step explanation:
To generate the sequence, substitute n = 1, 2, 3, 4, ..... into the rule
a₁ = 4(1) + 1 = 4 + 1 = 5
a₂ = 4(2) + 1 = 8 + 1 = 9
a₃ = 4(3) + 1 = 12 + 1 = 13
a₄ = 4(4) + 1 = 16 + 1 = 17
a₅ = 4(5) + 1 = 20 + 1 = 21
Answer: eight hundred ninety thousand, seven hundred four
Answer:
What happens if you put a booger on a tissue. The tissue starts to boogey dance.
Step-by-step explanation:
Answer:
(2 x - 3)^2 thus it's True
Step-by-step explanation:
Factor the following:
4 x^2 - 12 x + 9
Factor the quadratic 4 x^2 - 12 x + 9. The coefficient of x^2 is 4 and the constant term is 9. The product of 4 and 9 is 36. The factors of 36 which sum to -12 are -6 and -6. So 4 x^2 - 12 x + 9 = 4 x^2 - 6 x - 6 x + 9 = 2 x (2 x - 3) - 3 (2 x - 3):
2 x (2 x - 3) - 3 (2 x - 3)
Factor 2 x - 3 from 2 x (2 x - 3) - 3 (2 x - 3):
(2 x - 3) (2 x - 3)
(2 x - 3) (2 x - 3) = (2 x - 3)^2:
Answer: (2 x - 3)^2